Sebuah Upaya Pembacaan Poskolonial dengan Metode Dialog Imaginatif Antara Foto Soeharto “Piye Kabare, Penak Jamanku To?" dan Teks Keluaran 14:10-12; 16:1-3; 17:3 - Angela Pontororing (Indonesian Journal of Theology, 2016)
Around year 2013, Soeharto’s meme “Piye kabare, penak jamanku to?” was heavily distributed around society in many forms, such as stickers, t-shirts and also in internet. Even though New Order regime can be said as a regime colored with violence and oppression, Indonesian civilians still showing intention to bring back the New Order system rather than living in the crisis they’re facing at that time. The same symptoms can be seen in the exodus narration of the Israeli from Egypt. In the time of crisis, the Israeli cried their wish to go back to slavery in Egypt. To build a contextual theology that is more sensitive to actual socio-political issues, these symptoms need to be studied further. Therefore, this article uses a postcolonial perspective to read two texts which were born from two different contexts. Dialogical imagination was chosen as a method to draw these three things together in one critical analytical reading.